The potentıal causatıve factors ın dıscıtıs after lumbar macrodıscectomy - Özgen, Serdar; Konya, Deniz; Peker, Selçuk; Pamir, Necmettin (My University, 2003)
Objective: Development of discitis after lumbar discectomy is one of the most important complications of disc surgery. This retrospective study investigated the influence of potential contributing factors in 9 cases of postoperative discitis occurring in 2901 patients who underwent macrodiscectomy.
Keywords: Lumbar disc herniation, discectomy, discitis